The complete chloroplast genome of Eriocaulon sexangulare (Eriocaulaceae). Issue 1 (2nd January 2019) - Han, Bingqian; Tan, Guangwen; Hu, Zhenyang; Wang, Yongqi; Liu, Ying; Zhou, Renchao; Zhou, Qiujie
Abstract: Eriocaulaceae, a family of herbaceous plants in the order Poales, includes some well-known species used in traditional Chinese herbal medicine. The phylogenetic position of Eriocaulaceae in Poales remains controversial. In this study, we reported the complete chloroplast genome of Eriocaulon sexangulare (Eriocaulaceae) assembled from Illumina sequencing reads. The complete chloroplast genome was 151, 435 bp in length with 38.60% overall GC content, containing a large single copy (LSC) region of 81, 533 bp, a small single copy (SSC) region of 17, 114 bp and a pair of inverted repeat (IR) regions of 26, 394 bp. A total of 134 genes were annotated, including 88 protein-coding genes, 8 rRNAs, and 38 tRNAs. Phylogenetic analysis showed that E. sexangulare is most closely related to Syngonanthus chrysanthus (Eriocaulaceae) and the family Eriocaulaceae is sister to Mayacaceae.